"It Ain't Home Base No More:" Sentencing Reform and Dynamic County Jail Inmate Politics. (September 2022) - Caudill, Jonathan W.; Trulson, Chad R.; DeLisi, Matt; Marquart, James W.
Inmate politics in prisons has been well chronicled. Yet, little is known about the role of inmate politics in county jails. Utilizing data from a natural experiment and complied through longitudinal case study methods, this study observed the dynamic socio-political concepts of the county jail inmate environment that followed California's 2011 sentencing reform. Identifying those aspects of the jail inmate political system that shifted – enhancements in the role of race relations among inmates, an expansion of the inmate economy, and emergence of utilitarian violence – also permits a clearer understanding of the jail inmate political system.